Comparison of Physicochemical, Antioxidant Properties and Sensory Acceptance of Puree from Tamarillo and Tomato - Mohd Nor, Nur Zawin Nazihah; Kormin, Faridah; Mohamad Fuzi, Siti Fatimah Zaharah; Abu Bakar, Muhammad Abdul Latiff (Journal of Science and Technology, 2018)
Puree is well known as the best food ingredient to enhance flavour in cooking. Tamarillo (Cyphomandra betacea) is an underutilized fruit in Malaysia due to their bland and strong sour taste. Tomato (Lycopersicon esculentum) is a well-known fruit that grows throughout the tropical and commonly consumed vegetable fruit. The purpose of this study are to determine and do a comparison on the physicochemical properties (pH, total soluble solid (TSS), moisture content, ash, protein, fat and carbohydrates) in tamarillo and tomato puree. In addition, this study was conducted to evaluate the antioxidant properties of tamarillo and tomato puree by using TPC and FRAP assay and lastly to evaluate the consumers acceptance on the new product (tamarillo puree) using sensory evaluation by 9 point hedonic test. Based on the results, tamarillo puree has lower pH value (4.12±0.11), moisture content (89.24±0.004%), and fat content (0.2% wt/wt) as compared to tomato puree (pH: 4.48±0.08, moisture: 95.76±0.006%, fat: 0.3% wt/wt). Meanwhile, TSS value (9.30±0.20˚Brix), carbohydrate (7.584% wt/wt), protein (1.0% wt/wt) and ash content (1.976%) of tamarillo puree was higher as compared to tomato puree (TSS: 3.30±0.10˚Brix, carbohydrate: 3.064% wt/wt, protein: 0.09% wt/wt, ash: 0.786%). The TPC and FRAP value for tomato puree was 102.111±0.778mg of GAE/L and 1.786±0.013g of FSE/ml respectively, which were higher than tamarillo puree with value of 79.815±0.39mg of GAE/L and 1.344±0.016g of FSE/ml respectively. Likewise for TFC value, tomato puree was higher (9.389±0.394 RE/L) as compared to tamarillo puree (18.111±2.577 RE/L). Results showed the comparison of physicochemical properties, antioxidant properties as well as consumer acceptability.